2022
DOI: 10.1038/s41588-022-01052-9
|View full text |Cite
|
Sign up to set email alerts
|

Systematic characterization of gene function in the photosynthetic alga Chlamydomonas reinhardtii

Abstract: Most genes in photosynthetic organisms remain functionally uncharacterized. Here, using a barcoded mutant library of the model eukaryotic alga Chlamydomonas reinhardtii, we determined the phenotypes of more than 58,000 mutants under more than 121 different environmental growth conditions and chemical treatments. A total of 59% of genes are represented by at least one mutant that showed a phenotype, providing clues to the functions of thousands of genes. Mutant phenotypic profiles place uncharacterized genes in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
112
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(118 citation statements)
references
References 76 publications
5
112
0
1
Order By: Relevance
“…The green alga Chlamydomonas reinhardtii (Chlamydomonas hereafter, Figure 1A) is a powerful model system for studying the cell biology of photosynthetic eukaryotes. Its unicellular nature and microbial lifestyle allow for higher throughput than land plant model systems, enabling systematic large-scale analysis of gene and protein function (Fauser et al, 2022). As an evolutionary relative of land plants (Gutman and Niyogi, 2004; Merchant et al, 2007), Chlamydomonas has been a critical model system that has revealed conserved pathways and key principles of chloroplast biology including electron transport (Iwai et al, 2010), photosynthetic regulation (Depège et al, 2003), assembly of photosynthetic complexes (Minai et al, 2006), and chloroplast genome segregation (Kobayashi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The green alga Chlamydomonas reinhardtii (Chlamydomonas hereafter, Figure 1A) is a powerful model system for studying the cell biology of photosynthetic eukaryotes. Its unicellular nature and microbial lifestyle allow for higher throughput than land plant model systems, enabling systematic large-scale analysis of gene and protein function (Fauser et al, 2022). As an evolutionary relative of land plants (Gutman and Niyogi, 2004; Merchant et al, 2007), Chlamydomonas has been a critical model system that has revealed conserved pathways and key principles of chloroplast biology including electron transport (Iwai et al, 2010), photosynthetic regulation (Depège et al, 2003), assembly of photosynthetic complexes (Minai et al, 2006), and chloroplast genome segregation (Kobayashi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Previous pooled screens investigated the behavior of CLiP mutants in approximately 121 different screen conditions (Fauser et al 2022), which we sorted into 16 broad categories (Figure S3). Fauser et al (2022) used two significance thresholds for analysis, FDR < 0.3 and FDR < 0.05.…”
Section: Some Heat Tolerance Genes (Htgs) May Be Also Involved In Oth...mentioning
confidence: 99%
“…The Jonikas laboratory, which led the generation of the CLiP mutant library, together with collaborators, employed the CLiP library to screen for mutants deficient in photosynthesis (Li et al 2019) and 121 other different environmental/chemical conditions, including high temperatures (Fauser et al 2022). Fauser et al (2022) included high temperatures of 30, 35, 37 o C and also tested the effects of light intensities, CO2 concentration, and organic carbon availability on heat responses (Supplemental Dataset 1a). The pooled screens by Fauser et al (2022) have been foundational in using the CLiP mutant library under various screen conditions for functional genomics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, the species has been used as a powerful model for investigating the eukaryotic cell cycle (Cross and Umen 2015) and conserved mechanisms of sexual reproduction (Ning et al 2013; Fédry et al 2017), for discovery of optogenetic tools (Deisseroth and Hegemann 2017), and for in situ structural analyses by cryo-electron microscopy (Engel et al 2015; Freeman Rosenzweig et al 2017). Genome-wide mutant libraries form part of a growing suite of tools for exploiting high-throughput functional genomics approaches (Li et al 2019; Fauser et al 2022). As the most thoroughly studied green alga, Chlamydomonas also serves as an integral reference for the rapidly expanding fields of algal biology and biotechnology (Crozet et al 2018; Blaby-Haas and Merchant 2019).…”
Section: Introductionmentioning
confidence: 99%